Your Higgs number—how fundamental physics is connected to technology and societal revolutions. (14th January 2015) - Allen, Roland E; Lidström, Suzy
Abstract: Fundamental physics, as exemplified by the recently discovered Higgs boson, often appears to be completely disconnected from practical applications and ordinary human life. But this is not really the case, because science, technology, and human affairs are profoundly integrated in ways that are not immediately obvious. We illustrate this by defining a 'Higgs number' through overlapping activities. Following three different paths, which end respectively in applications of the World Wide Web, digital photography, and all modern electronic devices, we find that most people have a Higgs number of no greater than 3.